Robust Diagnostic Genetic Testing Using Solution Capture Enrichment and a Novel Variant‐Filtering Interface. Issue 4 (April 2014) - Watson, Christopher M.; Crinnion, Laura A.; Morgan, Joanne E.; Harrison, Sally M.; Diggle, Christine P.; Adlard, Julian; Lindsay, Helen A.; Camm, Nick; Charlton, Ruth; Sheridan, Eamonn; Bonthron, David T.; Taylor, Graham R.; et al.
<x xml:space="preserve">Abstract</x> We present two programs, AgileExomeFilter and AgilePindelFilter, which enable clinical scientists to rapidly and efficiently filter variants from next generation sequencing data. Using these tools a high diagnostic yield (42%) was obtained in a cohort of 24 primary ciliary dyskinesia (PCD) patients that underwent targeted exome analysis. Autozygosity mapping in the mutation negative cases revealed a homozygous truncating mutation in DNAH8, a presumptive new PCD gene. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>